IMPROVING COHESION OF THE STUDENTSÃ¢â¬â¢ SENTENCES THROUGH THE APPLICATION OF COHESION THEORY IN THE SENTENCE-BASED WRITING CLASS - Priyatmojo, Arif Suryo (Language Circle: Journal of Language and Literature, 2012)
This study was aimed at 1). describing what kinds of cohesive device mostly occured in the studentsÃ¢â¬â¢ sentences, 2). describing how to apply cohesion theory in the sentence-based writing class, and 3). finding out whether the use of cohesion theory gives its positive significance to cohesion of the studentsÃ¢â¬â¢ sentences. This is an action research study employing two cycles. The subject of the study was 24 students of group 2, in a class of SBW, and the object of the study was studentsÃ¢â¬â¢ sentences created by the students in the teaching and learning process. The result of the study shows that cohesive devices mostly employed by the students are references followed by lexical, conjunction and substitution. Moreover, the students never used ellipsis in the studentsÃ¢â¬â¢ sentences. In the teaching and learning process, cohesion theory was given to the students in two cycles. The first cycle focused on introducing the cohesion theory and its kinds of cohesive devices. Then, in the next cycle the students learned about Halliday and Hasan Taxonomy. Based on the result of the study, teaching SBW using cohesion theory gives its positive significance by varied cohesive device used by the students. It can be seen from the analysis of the studentsÃ¢â¬â¢ sentences from pre-test, paragraph 1, paragraph 2, paragraph 3 and post-test. The students also give positive responses upon its teaching and learning process using cohesion theory based on the pre and post-test questionnaire data. It is hoped that the result of the study gives positive contribution to the students in preparing them to write in bigger contexts such as paragraph-based writing, genre-based writng and academic writing in the next coming semesters.